2009
DOI: 10.1007/s00268-009-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Interactions of Interleukin‐10, Transforming Growth Factor β, and Vascular Endothelial Growth Factor in Esophageal Squamous Cell Carcinoma

Abstract: Overexpression of IL-10, TGF-beta, and VEGF plays an important role in ESCC and consequently leads to the frequent event of immune evasion in ESCC. TGF-beta is concomitantly overexpressed with IL-10 and with VEGF in ESCC. A stimulatory signal from TGF-beta to VEGF is necessary for VEGF to promote tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 48 publications
1
44
1
1
Order By: Relevance
“…Some studies have reported that there was no relationship between sTGF-β1 levels and disease progression [14,21]. However, in our study, serum levels of TGF-β1 tended to be higher in advanced oesophageal cancer than those in stage I and II.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Some studies have reported that there was no relationship between sTGF-β1 levels and disease progression [14,21]. However, in our study, serum levels of TGF-β1 tended to be higher in advanced oesophageal cancer than those in stage I and II.…”
Section: Discussioncontrasting
confidence: 52%
“…A number of studies have demonstrated enhanced tissue expression of TGF-β1 in many different malignancies, including breast [9], colorectal [10], small intestine [11], gastric [12] and oesophageal adenocarcinomas [13]. The overexpression of TGF-β1 mRNA in ESCC has also been demonstrated [14]. However, a little is known about the concentration of serum TGF-β1 (sTGF-β1) in ESCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, tumors have been shown to escape the anti-tumor immune responses by generating an immunosuppressed tumor microenvironment. Tumors often produce soluble immunosuppressive factors, such as TGFβ [13,68,69], VEGF [69,70], IL-10 [69,71], iNOS [72,73], PGE 2 [74,75], and gangliosides [76,77], that act on neutrophils and other tumor infiltrating immune cells. Often, progressive immunosuppression is observed at advanced tumor stages, which is partially mediated by tumor-infiltrating immunosuppressive immune cells such as regulatory T (Treg) cells, Th17 cells, regulatory dendritic cells, TAMs, TANs and MDSCs.…”
Section: Immunosuppression In the Tumor Microenvironmentmentioning
confidence: 99%
“…VEGF induces bone marrow-derived myeloid cell mobilization to the circulation and through VEGF-mediated upregulation of SDF1/CXCL12 in activated perivascular myofibroblasts, the myeloid cells are kept in close proximity to angiogenic vessels [223]. VEGF is upregulated in a wide variety of tumors [69,[224][225][226][227], as is CXCL12 [228]. CXCL12, that is also upregulated by hypoxia [229], augments CXCR4 expression on vascular endothelial cells [230] and attracts CXCR4 + cells, including neutrophils, to the tumor [223].…”
Section: Neutrophil Recruitment To the Tumor Microenvironmentmentioning
confidence: 99%
“…ESCC is characterized by profound immune dysfunction thought to be caused by cytokine production originating from tumor cells and host immune competent cells (19)(20)(21). In cancer patients, lymphopenia is the surrogate of impaired cell-mediated immunity, whereas neutrophilia is a response to systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%